MODEL PEMBELAJARAN RADEC DAN KOMPETENSI MUSIKAL: STUDI EKSPERIMEN PADA KEMAMPUAN MENGKOMPOSISI RITME SISWA KELAS IV SD - Andra Nata; Resa Respati; Anggit Merliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the effect of the RADEC (Read, Answer, Discuss, Explain, Create) learning model on fourth-grade students’ rhythmic composition skills. A true experimental method with a posttest-only control group design was applied to a sample of 50 students randomly divided into experimental (n = 25) and control (n = 25) groups. The performance test measured four musical creativity indicators: fluency, flexibility, originality, and elaboration. Findings revealed that the experimental group’s mean score (M = 58.50) was higher than the control group’s (M = 46.50). An independent t-test showed a p-value of 0.009 (< 0.05), indicating a significant positive effect of RADEC on rhythmic composition skills. The integration of body percussion during the Create stage enhanced kinesthetic engagement and creative exploration. These results suggest that RADEC is an effective instructional models for fostering creativity in elementary school music learning